2012
DOI: 10.1002/acr.21780
|View full text |Cite
|
Sign up to set email alerts
|

Differences in physical activity patterns in patients with spondylarthritis

Abstract: Objective. To study patient-reported physical activity in patients with spondylarthritis (SpA) and possible differences in physical activity patterns between the SpA subtypes and sexes. Methods. In 2009, a questionnaire including inquiries concerning physical activity was sent to patients with a SpA diagnosis (n ‫؍‬ 3,711). The World Health Organization (WHO) global recommendations of physical activity for health requiring 150 minutes of moderate-intensity physical activity (MI-PA) or 75 minutes of vigorous-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
67
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 39 publications
12
67
1
3
Order By: Relevance
“…These findings are in accordance with Haglund and colleagues, who found that lower disease activity (BASDAI), better physical function (BASFI), and better health-related quality of life (EuroQoL) were positively associated with meeting the World Health Organization recommendations of moderate-intensity and/or vigorous-intensity physical activity in a heterogeneous group of spondyloarthritis patients [4]. Some additional support for these relationships can be obtained from intervention studies concerning exercise programs and physical therapy in AS.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are in accordance with Haglund and colleagues, who found that lower disease activity (BASDAI), better physical function (BASFI), and better health-related quality of life (EuroQoL) were positively associated with meeting the World Health Organization recommendations of moderate-intensity and/or vigorous-intensity physical activity in a heterogeneous group of spondyloarthritis patients [4]. Some additional support for these relationships can be obtained from intervention studies concerning exercise programs and physical therapy in AS.…”
Section: Discussionsupporting
confidence: 90%
“…To improve face and content validity, the questionnaire was tested in focus groups with a total of twenty patients with different SpA subgroup diagnoses. This resulted in minor corrections in the questionnaire in order to improve understanding [25].…”
Section: Questionnairesmentioning
confidence: 99%
“…In fact, many patients with axial SpA are already physically active; however research showed that a substantial proportion of patients did not reach the public health recommendations for physical activity (24), especially with regard to the intensity of CRT (25). Therefore, the evidence for the effectiveness and safety of vigorous CRT may also be an additional facilitator, and, in fact, our study showed that a majority of rheumatologists would refer more patients to the exercise groups if vigorous CRT was included.…”
Section: (5)mentioning
confidence: 99%